2019
DOI: 10.11646/zootaxa.4642.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetics of snailfishes (Cottoidei: Liparidae) based on MtDNA and RADseq genomic analyses, with comments on selected morphological characters

Abstract: Phylogenetic relationships of snailfishes of the family Liparidae were analyzed on the basis of two sets of molecular sequence data: one from the mitochondrial DNA cytochrome c oxidase subunit one gene (COI) and another from restriction-site associated genome-wide sequences (RADseq). The analysis of COI sequence data from at least 122 species of 18 genera from the Pacific, Atlantic, and Southern oceans resulted in a moderately well-resolved phylogeny among the major clades, albeit with significant polytomy amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 69 publications
9
85
0
Order By: Relevance
“…A more recent publication covering a molecular phylogeny of the Liparidae (Knudsen et al 2007) was also based on a very restricted number of species (24), all from the northern hemisphere. The extremely diverse liparid fauna A B C from the southern hemisphere, comprising about 150 species (Andriashev 1986(Andriashev , 2003Andriashev and Stein 1998;Stein et al 2001;Stein 2012aStein , 2012b remains almost unstudied in internal anatomy although some molecular investigations have been recently published (Duhamel et al 2010;Orr et al 2019). As a result, the current paradigm of the genus-level systematics of the Liparidae may change drastically after a comprehensive morphological and molecular study of this family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent publication covering a molecular phylogeny of the Liparidae (Knudsen et al 2007) was also based on a very restricted number of species (24), all from the northern hemisphere. The extremely diverse liparid fauna A B C from the southern hemisphere, comprising about 150 species (Andriashev 1986(Andriashev , 2003Andriashev and Stein 1998;Stein et al 2001;Stein 2012aStein , 2012b remains almost unstudied in internal anatomy although some molecular investigations have been recently published (Duhamel et al 2010;Orr et al 2019). As a result, the current paradigm of the genus-level systematics of the Liparidae may change drastically after a comprehensive morphological and molecular study of this family.…”
Section: Discussionmentioning
confidence: 99%
“…It includes the nominal genera Paraliparis Collett, 1879; Rhodichthys Collett, 1879; Psednos Barnard, 1925;Genioliparis Andriashev & Neelov, 1976;Odontoliparis Stein, 1978;Praematoliparis Andriashev, 2003;Aetheliparis Stein, 2012;Rhinoliparis Gilbert, 1896;Lipariscus Gilbert, 1915 andEdentoliparis Andriashev, 1990. Although accepted by some authors (Balushkin 1996;Andriashev 2003;) the last three genera are usually synonymized with Paraliparis (Kido 1988;Nakabo 2002;Duhamel et al 2010;Stein 2012a;Orr et al 2019). The monotypic Praematoliparis from the Strait of Magellan, Genioliparis (including Odontoliparis) with three north-eastern Pacific and Antarctic species and Aetheliparis with two species from the North Atlantic and South Pacific represent unusual genera sharing certain unique features (low dorsal and anal fin-ray count, unsegmented fin rays in Praematoliparis; predatory adaptations in Genioliparis; upturned mouth with a significantly concave lower jaw, enlarged gill cavity and remote position of pectoral fins in Aetheliparis); they are not discussed beyond this observation.…”
Section: A B Cmentioning
confidence: 99%
“…Paraliparis Collett, 1879 and related genera have been variously synonymized in previous studies. Although Kido (1988) combined 11 genera under Paraliparis following a phylogenetic analysis based on osteological characters, later authors, e.g., Mecklenburg et al (2002), Chernova et al (2004), and Nakabo and Kai (2013), considered six of the included genera, e.g., Elassodiscus Gilbert & Burke, 1912, Rhinoliparis Gilbert, 1896, and Lipariscus Gilbert, 1915 In a recent molecular phylogenetic study, Orr et al (2019) confirmed that Paraliparis was paraphyletic, requiring further taxonomic revision. Nevertheless, present members of the genus are generally distinguishable by the following characters: single nostril; one suprabranchial pore, six branchiostegal rays, more than two rays in the lower lobe of the pectoral fin, and the absence of a pelvic disk, a pseudobranch, a coronal pore and a barbel or a skin flap on the head (Stein et al 2001;Stein 2012;Murasaki et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the family Liparidae (snailfishes), comprising over 430 species in ca 30 genera, exhibit great diversity in morphology, as well as in geographic and habitat range ( Chernova et al 2004 ; Nelson et al 2016 ; Orr et al 2019 ), and they occur worldwide in warm-temperate to cold water habitats ranging from the intertidal to depths exceeding 8,000 m ( Nelson et al 2016 ; Gerringer et al 2017 ). Paraliparis Collett, 1879 and related genera have been variously synonymized in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The sequences (deposited on GenBank, MN509400 and MN509401) were analysed with available COI data on GenBank using BLAST, a maximum likelihood phylogenetic approach (Stamatakis ) and also simple pairwise distances (see Garcia et al ; BLAST available online ). Taxon sampling for the phylogenetic analysis was based on the BLAST results against available sequences on GenBank and the studies by Knudsen et al () and Orr et al (). The egg (SIO‐BIC BI1369; MN509400) sequenced from the Jaco Scar xenophyophore ( Reticulammina ) was less than 3% distant from a series of Paraliparis spp.…”
mentioning
confidence: 99%